Review of Fiqh Siyasah on the Implementation of Mayor's Regulation No. 12 Year 2011 Concerning Retribution of Licenses at the Selling of Alcoholic Beverages in Medan City - Muhammad Rizal; Deasy Yunita Siregar (RIRAI Publisher, 2023)
In Islam it is not very good and has an effect in the future. Therefore, both in essence and in use, alcoholic beverages are qat'i forbidden in the Qur'an and the sunnah of the Prophet SAW. Therefore beer and so on can be considered haram. That's why it can't be touched at all. The study of Fiqh Siyasah covers aspects of regulating the relationship between citizens and citizens, the relationship between citizens and state institutions, and the relationship between state institutions and state institutions. This study aims to review Fiqh Siyasah on the implementation of Mayor Regulation no. 12 of 2011 concerning Levies for Permits for Selling Alcoholic Drinks in Medan City. Using a descriptive method, the results of this study indicate that the Fiqh Siyasah review of the implementation of Mayor Regulation No. 12 of 2011 concerning the retribution for permits for selling alcoholic beverages Medan City, which has not been carried out in accordance with Fiqh Siyasah because Islam itself forbids alcoholic beverages because there are more bad things that caused by consuming alcoholic beverages rather than the good.